Diagnosis and Therapy of Infectious Encephalitis in Children: A Ten-Years Retrospective Study. Issue 6 (10th May 2021) - Pata, Davide; Buonsenso, Danilo; Frasca, Giampiero; Lazzareschi, Ilaria; Salerno, Gilda; Turriziani Colonna, Arianna; Mariotti, Paolo; Valentini, Piero
Abstract : Background: Infectious encephalitis represents a rare but potentially severe clinical condition. However, limited international data are available in pediatric age. Methods: We conducted a retrospective study to review (a) the clinical presentation; (b) laboratory, radiology, and neurophysiology findings; (c) the correlations between these exams and outcome; and (d) the therapy performed. Results: Fifty-six patients were enrolled [22 female (39.6%), mean age 4.7 years, IQR 0.7–8.7 years], 19.6% presented neurologic sequelae. HSV was the single most frequently isolated pathogen (19.6%), although in most cases, the etiology remained undefined. 41.1% children presented prodromal before the development of neurologic signs. Fever was the most frequent constitutional symptom (83.9% of cases). Cerebrospinal fluid was normal in 48.5% of cases and electroencephalograpy in 24.5% cases. Brain computed tomography scans was normal in 33 (91.7%) cases, while cerebral magnetic resonance imaging (MRI) showed pathologic findings in 62.5% of cases. MRI was the only parameter associated with neurologic sequalae [ P  = 0.01; OR, 8.1 (95% CI: 1.52–42.84)]. Conclusions: Pediatric encephalitis is a heterogeneous entity with nonspecific clinical and laboratory findings, with undefined etiologies in most times. MRI can play a primary role, both on a diagnostic and prognostic point-of-view, and its role should be implemented and made more accessible. Further studies are needed to define the exact role and timing of steroids.